GLOBAL EXPERIENCE OF EFFICIENT AGRICULTURAL WASTE MANAGEMENT - Dubnevych , Ю.; Voinycha , Л. (Bulletin of Lviv National Environmental University. Series "AIC Economics", 2023)
Agro-industrial production can generate a variety of wastes, each having different components and properties. Some of the most common sources of agro-based waste include crop residues, animal waste, residues from feed production, waste from biofuel production, waste from production of fertilisers and crop protection products. After harvesting, there may be plant residues that are not suitable for consumption or use. Animal slaughter produces a large amount of waste, such as bones, skins, organs, etc. Production of animal feed can generate waste, such as stalks, straws, and grain husks. Biofuel production from grain crops can lead to generation of waste in the form of residues from biomass processing. Processing and preservation of food produce waste, such as shells, corks, seeds, etc. After products and materials are used, their residues can become waste that needs to be disposed and removed. Production of fertilisers and crop protection products can generate waste, such as processed liquids, plant material residues, etc. All these sources may differ depending on the type of agro-industrial activity and equipment used. Agro-industrial waste management is an important task for ensuring environmental safety and conservation of natural resources. The main goal of agro-industrial waste management is to reduce waste and use it as a resource for producing new products or energy. Agro-industrial waste management presupposes planning, organization, control, and implementation of measures for collecting, processing, use and disposal of waste produced during agro-based activities. The work explores foreign experience of the agro-industrial waste management in such countries as Germany, Switzerland, Sweden, the USA, China, and Japan, in terms of the possibility of its further implementation in Ukraine. The article dwells on the peculiarities of effective management of agro-industrial waste for each country. The article summarises the conceptual foundations of the agro-industrial waste management system abroad, which allowed to identify common features inherent in almost all developed countries, namely: preference for innovative methods of waste disposal, introduction of recycling programmes, and reduction of the processes that have a heavy load on the environment.